Combined of Motive Balapak Design in Development of Songket as Traditional Weaving Fabric on Minangkabau Culture - Budiwirman; Syeilendra (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the behavior and culture of the Minangkabau people concerning the existence of Songket. The symbol used in Songket can be interpreted as a guide to people's lives in Minangkabau. Data was qualitatively collected from the village of Silungkang, Solok Regency, West Sumatra, Indonesia, by using ethnographic methods. The object of this research is the Minangkabau Songket fabric, which is designed with a self-image symbol. The obtained data were qualitatively analyzed through reduction, presentation, and drawing conclusions/verification. The researcher moved between the four "axes" of the coil and continued until the research data were at the saturated stage or had been able to answer the research question. The results showed that Songket woven fabric is a major part of the traditional clothing of the ethnic Minangkabau stakeholders with a special place and a beautiful shape of sparkling gold thread. It is also decorated with various plant and animal motifs and closely related to the existence of the Penghulu and Bundo Kanduang. This outfit consists of symbols that are translated into symbolic values and are meaningful to the Minangkabau system of life and society.